Diseño y construcción de una trituradora para procesamiento de 10kg/h de botellas PET accionada por pedaleo para propiedad horizontal de Bogotá (2024)
This project focuses on the design and construction of a pedal-powered PET bottle crusher to process plastic waste in a horizontal property in Bogotá. The properties of PET were investigated to ensure its suitability for the crushing and reuse process. Using computer-aided design (CAD) tools, a mechanical model was developed to optimize pedal power, ensuring ergonomics and adaptability in a residential environment.